A Physically Motivated Framework to Compare Pair Fractions of Isolated Low- and High-mass Galaxies across Cosmic Time - Katie Chamberlain; Gurtina Besla; Ekta Patel; Vicente Rodriguez-Gomez; Paul Torrey; Garreth Martin; Kelsey Johnson; Nitya Kallivayalil; David Patton; Sarah Pearson; George Privon; Sabrina Stierwalt (The Astrophysical Journal, 2024)
Low-mass galaxy pair fractions are understudied, and it is unclear whether low-mass pair fractions evolve in the same way as more massive systems over cosmic time. In the era of JWST, Roman, and Rubin, selecting galaxy pairs in a self-consistent way will be critical to connect observed pair fractions to cosmological merger rates across all mass scales and redshifts. Utilizing the Illustris TNG100 simulation, we create a sample of physically associated low-mass (10 ^8 < M _* < 5 × 10 ^9 M _⊙ ) and high-mass (5 × 10 ^9 < M _* < 10 ^11 M _⊙ ) pairs between z = 0 and 4.2. The low-mass pair fraction increases from z = 0 to 2.5, while the high-mass pair fraction peaks at z = 0 and is constant or slightly decreasing at z > 1. At z = 0 the low-mass major (1:4 mass ratio) pair fraction is 4× lower than high-mass pairs, consistent with findings for cosmological merger rates. We show that separation limits that vary with the mass and redshift of the system, such as scaling by the virial radius of the host halo ( r _sep < 1 R _vir ), are critical for recovering pair fraction differences between low-mass and high-mass systems. Alternatively, static physical separation limits applied equivalently to all galaxy pairs do not recover the differences between low- and high-mass pair fractions, even up to separations of 300 kpc. Finally, we place isolated mass analogs of Local Group galaxy pairs, i.e., Milky Way (MW)–M31, MW–LMC, LMC–SMC, in a cosmological context, showing that isolated analogs of LMC–SMC-mass pairs and low-separation (<50 kpc) MW–LMC-mass pairs are 2–3× more common at z ≳ 2–3.